The evolution of business in the cyber age : digital transformation, threats, and security - Chowdhry, Divya Gupta; Verma, Rahul, 1989-; Mathur, Manisha (Oakville, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2020)
"This book has a two-fold mission: to explain and facilitate digital transition in business organizations using information and communications technology and to address the associated growing threat of cyber crime and the challenge of creating and maintaining effective cyber protection. The book begins with a section on Digital Business Transformation, which includes chapters on tools for integrated marketing communications, human resource workplace digitation, the integration of the Internet of Things in the workplace, Big Data, and more. The technologies discussed aim to help businesses and entrepreneurs transform themselves to align with today's modern digital climate. In the section on Cyber Threat and Cyber Security, the volume goes on to address the growing challenges of keeping your online presence safe and secure, protecting your data along with that of your customers, detecting cyber attacks, and more. It considers the challenges of cyber safety in cloud computing and the interconnectedness of devices across platforms. The Evolution of Business in the Cyber Age: Digital Transformation, Threats, and Security provides a wealth of information for those involved in the development and management of conducting business online as well as for those responsible for cyber protection and security. Faculty and students, researchers, and industry professionals will find much of value in this volume."--
Digital Workplace: The Human Interface / Debashis Ghosal and Shulagna Sarkar -- Helping Entrepreneurs and Small Businesses Make the Digital Transformation / Sugandha Soni Chopra -- Digital Transformation Using ICT Tools for Blended Teaching and Learning / S. Karkuzhali and S. Senthilkumar -- A Critical Analysis of E-HRM as a Strategic Capability Builder / B.C. Sinha -- 3Cs of International Market Penetration Through IMC: Culture,Change, and Connect / Jyoti Kukreja -- Internet of Things (IoT) and the Digital Business Environment: A Standpoint Inclusive Cyber Space, Cyber Crimes, and Cybersecurity / Anand Nayyar, Rudra Rameshwar, and Arun Solanki -- Big Data: Analytics, Technologies, and Applications / E. Sweetline Priya -- Cyber Threat Detection and Secured Alternative Technology: A Survey / S. Anitha and Hemanth G. Kumar -- Ransomware Evolution: Solving Ransomware Attack Challenges / Muhammad Ubale Kiru and Aman Jantan -- Global Challenges and Role of ICT in Empowerment of Teachers / Shweta Tripathi -- Cybersecurity and the Internet of Things: Anticipating the Leverage of Cyber Crimes with Interconnected Devices / A. Reyes-Menendez, J.R. Saura, and P. Palos-Sanchez -- Cloud Computing and Security / Dinesh Goyal and R.S. Rajput -- Unpacking Cybersecurity Trends / Vannie Naidoo and Rahul Verma.
OCLC-licensed vendor bibliographic record.
Keywords: Business enterprises -- Computer networks -- Security measures; Confidential business information -- Security measures; Computer security; Information technology -- Management; BUSINESS & ECONOMICS / Development / Business Development; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science